The Influence of Green Accounting and Corporate Social Responsibility Publications on Corporate Social Responsibility Disclosure with Financial Performance as a Moderating Variable - Intan Rahma Sari; Muliyani; Sri Putri Winingrum W.A (MultiTech Publisher, 2025)
The purpose of this study is to evaluate the